VISUALISASI KETIDAKBERDAYAAN MASYARAKAT SEBAGAI SASARAN PEMBANGUNAN - Tamrin Kamal (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
Powerlessness is the inability of a person or group to change their destiny either due to internal or external factors so that it affects and raises the complexity of the problem. The visualization of powerlessness if narrated can be seen in economic, social, cultural and legal aspects. The solution offered in minimizing powerlessness is empowerment, as an effort to help local people who are powerless in various aspects such as poor living (cultural and structural), unemployment, low human resources, limited natural resources and others. Empowerment is directed so that they can help themselves, or efforts to guide the community so that they consciously learn to lead themselves, solve their own problems, according to their own potential and the potential of existing local resources. This is where the opportunity for social workers (social workers) as an extension of the government or social organizations, to take part in empowerment efforts. Moreover, higher education institutions are concerned with empowerment efforts